The formation of NeH+ in static vacuum mass spectrometers and re-determination of 21Ne/20Ne of air. (15th October 2019) - Györe, Domokos; Tait, Andrew; Hamilton, Doug; Stuart, Finlay M.
Highlights: Controls on NeH + formation are determined, and 20 NeH + formation is precisely quantified on the basis of measured 22 NeH + . 21 Ne/ 20 Ne of air has been re-determined to be 0.002959 ± 0.000004 (0.14%, 1σ). The lower uncertainty of air 21 Ne/ 20 Ne and better precision of Ne isotope analyses significantly reduces the uncertainty of Ne concentration measurements, essential for development of cosmogenic and radiogenic dating applications. Abstract: Air-derived neon is used for routine calibration of magnetic sector mass spectrometers, principally for determining sensitivity and mass discrimination for Ne isotope determinations. The commonly accepted 21 Ne/ 20 Ne ratio of air (0.002959 ± 0.000022; Eberhardt et al. (1965) does not take account of the contribution of 20 NeH + at m/z = 21. Honda et al. (2015) and Wielandt and Storey (2019) have recently re-determined the 21 Ne/ 20 Neair by resolving 20 NeH + from 21 Ne + . The 21 Ne/ 20 Neair values of the two studies differ by 1.8%, beyond the uncertainty of the measurements (± <0.1%). We have developed a protocol for precise determination of NeH + in air using a low-resolution Thermo Fisher ARGUS VI mass spectrometer and use it to re-determine the 21 Ne/ 20 Ne of air. 22 NeH + / 22 Ne + measured at different H2 + and Ne + intensities reveal that (i) the partial pressure of H2 + in the instrument is the primary control on NeH + production, and (ii) increasing Ne + pressure suppresses the formation of NeH + . Calibration curves of 22 NeH + / 22 Ne + vs. 22 Ne + at constant H2 + are used to calculate the 20 NeH + production in aliquots of air-derived Ne and allow for hydride correction at m/z = 21. The fully isobaric interference-corrected Ne isotope compositions measured at different electron energy (eV) settings define a single mass fractionation line in 22 Ne/ 20 Ne vs. 21 Ne/ 20 Ne space. The 20 NeH + / 21 Ne + ratio varies between 0.4% (90 eV) and 2.3% (60 and 70 eV). Correcting for 20 NeH + assuming 22 NeH + / 20 NeH +  =  22 Ne/ 20 Ne yields an over-correction of up to 0.7% and the data do not plot on a single mass fractionation line. Our study defines 21 Ne/ 20 Neair to be 0.002959 ± 0.14% (1σ) assuming 22 Ne/ 20 Ne = 0.102 (Eberhardt et al., 1965). This overlaps the value determined by Wielandt and Storey (2019), albeit with a slightly higher uncertainty. However, our value is statistically more robust and accounts for the dependency on hydride formation by Ne partial pressure. From this we conclude that high precision Ne isotope ratio determinations in future require the quantification of 20 NeH + . The improved precision of air 21 Ne/ 20 Ne will result in more precise cosmogenic 21 Ne surface exposure and (U + Th)/Ne ages.